Narrativas e conhecimentos históricos substantivos: um estudo com alunos do 9º ano do município de Tailândia/PA - NANEZ, Otto Jorge da Silva (Universidade Federal do Pará, 2019)
The aim of the study was to understand how elementary school students mobilize elements and operations of historical thought when challenged to narrate the history of black slavery in Brazil. The task faced by the research subjects provoked a series of cognitive movements: selecting events, characters, spaces and concepts in the long temporality, interpreting them and articulating them in an explanatory and coherent account. To achieve the proposed objectives, the investigation dialogued with the theories of the historian Jörn Rüsen and with the reflections of the field of historical education, discussing the specificities of the narrative in the production of historical knowledge and its relationship with the Historical learning and the formation of historical thought/consciousness. In the methodological course of qualitative nature, we attempted to articulate the contributions of Rüsen with referential from empirical researches in order to subside the analysis of the collected material. Twenty-three students from a 9th grade class from a municipal school in Thailand, Pará, participated in the study. The description and analysis of historical markers (substantive content, historical, spatial and temporal agents), characterized as structural substantive historical concepts and the way they articulate in the collected narratives were performed. The analysis and reflection made it possible to highlight the way students apprehend their historical knowledge about the historical concept of black slavery in Brazil, how they mobilize historical markers and basic notions of thought Historical as those of explanation, causality and relations between the temporal dimensions, which can help researchers and teachers in the task of understanding the processes of formation of thought and historical consciousness.